Utility of Esophageal Ultrasound-guided Biopsy of Mediastinal Lymph Nodes in Diagnosis of Childhood Tuberculosis. Issue 5 (8th April 2022) - Cohen, Jonathan Marc; Banks, Matthew; Kon, Onn Min; Eisen, Sarah
Abstract : A 6-year-old boy with autistic spectrum disorder was diagnosed with tuberculosis infection following contact tracing of his mother who had isoniazid-resistant pulmonary tuberculosis. He progressed to develop mediastinal lymphadenopathy causing a persistent cough. He was too small to undergo endobronchial ultrasound-guided biopsy. As an alternative, he underwent esophageal endoscopic ultrasound-guided biopsy, leading to confirmation of the diagnosis. We believe this approach to diagnostic biopsy is underrecognized in pediatric practice, and highlight its utility with this case and a brief literature review.